Two-Sided Markets: Apples Digital Application Platform (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2013)
Two-sided markets (or platforms) are defined as the platforms that provide goods or services to two distinct groups of customers, and that intermediate the transactions between these groups. Such platforms are of great importance in todays global business world and considerable amount of value is created by these platforms. The success of numerous firms in the business world, including but are not limited to Google, eBay, Amazon, Microsoft, Apple, Sony PlayStation, Visa, is mainly due to the advantages provided by the two-sided platforms. This paper is devoted to the two-sided markets phenomenon, its basic characteristics, architecture as well as mechanism. The paper explains the aforementioned information regarding two-sided markets by providing the case from Apples digital application platform. Furthermore, Apples competitive advantage stemming from this platform has been articulated by the theoretical perspective provided by the Resource Based View (RBV).